Correlates of early attrition from school sports clubs in male senior high school students: a 2.4-year follow-up study - Jindo, Takashi; Kitano, Naruki; Nagata, Koki; Nakahara-Gondoh, Yuichi; Suzukawa, Kazuhiro; Nagamatsu, Toshiya (Frontiers in Sports and Active Living, 2023)
The correlation between early attrition and school sports clubs has been underexplored. This study aims to clarify the correlates of early attrition from school sports clubs at a private male senior high school in Fukuoka Prefecture, Japan. Of the 928 first-year students, 331 belonging to the school's sports clubs were included in this study. A baseline survey was conducted in May 2017 and a followup survey was conducted in October 2019. This study defined early attrition as a student who quit a sports club earlier than April in their third year. Examined correlates for early attrition consisted of biological, intrapersonal, interpersonal, and institutional factors. We used univariate logistic regression analysis, in which early attrition was the response variable and the examined correlates were the explanatory variables, and calculated the odds ratios (OR) and 95% confidence intervals (CI). Overall, 232 students (85.0%) continued to participate in sports clubs after April of their third year, and 41 students (15.0%) experienced early attrition. Statistically significant correlates for early attrition were weight (OR = 0.94, 95% CI = 0.90-0.98), body mass index (OR = 0.84, 95% CI = 0.74-0.97), experience of injury or disability (OR = 0.40, 95% CI = 0.19-0.87), athletic achievement (OR = 0.29, 95% CI = 0.13-0.62), and duration of experience of the sport (OR = 0.99, 95% CI = 0.98-1.00). Our findings suggest that the school officers or family members of students should recognize the possibility of early attrition and provide appropriate support if a student experiences early attrition. The athletic level or norms of school sports club activities may differ among other schools and sports clubs; therefore, it is necessary to examine whether our findings are applicable to other schools and sports clubs.